Liturgy and law in a Dalmatian city: the bishop's book of Kotor : (Sankt-Peterburg, BRAN, F. no. 200) - Gyug, Richard (Monumenta liturgica Beneventana, 2016)
"The major parts of the manuscript Sankt-Peterburg, Biblioteka Rossijskoi Akademii Nauk, F. no. 200, were written in Beneventan script in the mid-twelfth century, perhaps specifically for the dedication in 1166 of the new cathedral of Kotor in southern Dalmatia, now Montenegro. The manuscript has two principal parts: a lectionary with epistles and gospels for major feasts of the liturgical year, and a pontifical with ceremonies proper to a bishop. The book functioned as a liturgical compendium for the use of the cathedral and bishop of Kotor. While the manuscript continued in use, over the course of two or three generations after its composition two gatherings of sermons were added to the codex, and ecclesiastical documents and communal statutes were copied in the margins and on blank pages of the bishop's book. The manuscript's contents and its layers of composition and use are significant sources for the study of the liturgy and culture of the southern Dalmatian coast, and reveal a complex history of liturgical influences and creativity. The Lectionary preserves conservative practices; the Pontifical re-works texts from Rome, southern Italy and Norman Sicily in unique and creative ways; the sermons are unusual new texts; and the documentary additions shed light on the history of the city and region. The introduction provides an extensive history of Kotor and its church, a codicological analysis of the manuscript and discussion of its contents, with particular attention to the sources of the liturgical items and their arrangement. The edition includes transcriptions with a critical apparatus and an apparatus of parallel citations for the lectionary, pontifical, sermons and documents. The flyleafs and palimpsest sections of the manuscript are analyzed or edited in the introduction."--